Ser forrozeiro em Caruaru: prática musical, mudança e continuidade na "Capital do forró" - Silva, Philipe Moreira Sales (2017)
Caruaru, located in the Agreste region in Pernambuco, is well known for its diversity in popular culture, highlighting the visual arts, dance, literature, theater and music. In this cultural diversity, a song, represented by forró, gained a special emphasis in the city because a projection of the title "Capital of forró" that describes the declarations of the communities, popularized in the urban zone from the decade of 1960. As of recognition that the city acquired as an important center of the musical practices related to the forró, this research aimed to object to investigate the development process of this musical genre in Caruaru from the idea that the musical making in the city is built through the process of change and musical continuity. This construction is discussed in two moments: at first, the forró in Caruaru in the past, making a historical reconstruction of how this genre was gaining space in the city from the 1950s until the recording of the song "Capital of Forró" by the Trio Nordestino. And then, forró in Caruaru in the present, which begins from the structural changes of the June festivals, passing through the process of change in forró music, until the current practices of the forró musicians that have as main period, for their performances, the month of June. This thesis is divided in four chapters that bring discussions about the objective proposed for this research, approaching in chapter 1 methodological and conceptual issues, in chapter 2 the construction of forró as a genre of Brazilian music, in chapter 3 its development in Caruaru, and finally in chapter 4 the forró musical practices in the city today.